A Tiny, Long-Distance Hunter - Cerda-Villablanca, E; Gordillo-Zavaleta, L (American Association for the Advancement of Science, 2024)
Lacrymaria olor cytoskeleton and membrane "origami" enables rapid cell hyperextension